The Loughborough 'Mansfield Hosiery' Strike, 1972: Deindustrialization, Post-war Migration, and Press Interpretation. (2nd January 2022) - Collinson, Marc
ABSTRACT: Recent historiographical trends have ensured the continued relevance of the strike at the Mansfield Mills' hosiery factory in Loughborough in 1972. How this dispute, one of three in the East Midlands in two years dubbed 'race strikes' by the press, gained notoriety and were interpreted as an exemplar of British working-class racism requires re-evaluation. The article uses sources underutilized in previous studies, including the archive of the National Union of Hosiery and Knitwear Workers (NUHKW), to better understand the industry, the traditions of the hosiery craft, and how its processes of training and promotion differed from other industries that experienced 'race strikes'. This article relocates the dispute within the processes of deindustrialization, demographic and social change, workplace culture, and the importance of press reportage in shaping interpretations.